Breaking the Silence: Understanding and Addressing High School Students’ Hesitation to Speak in English - Chaimae Fertat; Yazid EL Iraqi; Hind Brigui (Journal of English Language Teaching and Linguistics, 2026)
This research paper aims to investigate students’ reluctance to speak in English classes. Most secondary education teachers struggle with the issue of having students involved in speaking activities. The purpose of this paper is to study the correlation between students’ lack of motivation and reluctance to speak in English classes and to suggest ways to help teachers motivate their students to speak. An observation as well as a questionnaire were used to explore the research questions. Questionnaires were submitted to teachers while students’ behaviors inside English classes were observed and analysed. The findings show that motivation does, in fact, determine students’ engagement in speaking activities. They also reveal that there is a correlation between teachers not teaching speaking as a separate skill and students’ hesitation to speak in class. More importantly, among the implications of the current study is that adopting a learner-centered approach in teaching speaking provides a wide range of solutions to reach out to students and improve their learning experience.